2016
DOI: 10.1140/epjp/i2016-16144-1
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational collapse in f (R) gravity for a spherically symmetric spacetime admitting a homothetic Killing vector

Abstract: The gravitational collapse of a spherical distribution, in a class of f(R) theories of gravity, where f(R) is power function of R, is discussed. The spacetime is assumed to admit a homothetic Killing vector. In the collapsing modes, some of the situations indeed hit a singularity, but they are all covered with an apparent horizon. Some peculiar cases are observed where the collapsing body settles to a constant radius at a given value of the radial coordinate.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…In this appendix, we give the detail expressions of the physical quantities of the collapsing matter cloud in terms of the metric functions. More precisely, we give the values for ( 10)-( 13), and other quantities like the expansion scalar ( 8) and the Misner-Sharp mass function (27).…”
Section: Data Availabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…In this appendix, we give the detail expressions of the physical quantities of the collapsing matter cloud in terms of the metric functions. More precisely, we give the values for ( 10)-( 13), and other quantities like the expansion scalar ( 8) and the Misner-Sharp mass function (27).…”
Section: Data Availabilitymentioning
confidence: 99%
“…In the context of inhomogeneous LTB models in GR, these issues have been considered in great detail for various matter models including dust and viscous fluids [30,31]. The stellar collapse of stellar collapse in f (R) gravity using different forms of f (R) function and different matter distributions may be found in [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Although different type of f (R) models may be considered, only the ones which are in agreement with the standard cosmological observations should be of interest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The theory can describe the inflationary stage and dark energy-dominated stage, in which the late-time cosmic acceleration is realized [ 59 , 60 , 61 ]. A static spherically symmetric solution is discussed in [ 62 , 63 , 64 ], whereas studies on gravitational collapse can be found in [ 65 , 66 ]. Several black holes are derived in the framework of [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ] and their physical consequences are discussed in [ 79 , 80 , 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%